Participatory Processes as Unreliable Narrators: Political Legitimacy and Governance Narratives in the Social OMC Peer Review Process - Dion Curry (Decentring European Governance, 2019)
This paper explores the development of governance narratives focused on governing processes as a way of determining political legitimacy. It aims to explore the following questions: theoretically, how does the idea of decentred governance square with legitimating political processes? How do EU-level coordinating governance processes affect conceptions of political legitimacy? Does interpreting governance through a legitimating lens enhance our understanding of these EU-level processes? The paper develops a new ‘decentred’ analytical framework for understanding governance that positions it as a legitimating force that affects and is affected by relationships between actors (policy inputs), institutional structures (policy throughputs) and policy outputs. It uses this framework to analyse the peer review process of the Social Open Method of Coordination, a non-binding, coordinating instrument used by the EU and its Member States in the area of social policy. The research draws on a participant and text analysis of 65 Social OMC peer reviews held from 2008 to present. It uses the goals and summaries of these reviews to assess whether they focus on improving inputs (participation), throughputs (process) or outputs (policy outcomes) and how this focus then affects the shape of the peer reviews as a governance process. It finds that, as a governance process, the peer reviews lack a clearly defined governance narrative. While it does show a clear shift from focusing overwhelmingly on policy outputs to including participatory rhetoric, this is not always indicative of a widening of focus to include input legitimacy. Instead, there are clearer linkages between narratives of the peer reviews as output-focussed processes and the inclusion of throughput mechanisms into the narrative. This illustrates a potential disconnect between the stated goals of the process as an inclusive, participative one and what it accomplishes in narrative and practice, creating a potential governance mismatch and decoupling between governance inputs and outputs.